Investigating Students’ Reading Interest on English Reading Materials through Their Reading Habits during Pandemic - Slamet Wahyudi Yulianto; Diah Hanah; Khofifah Lisniyanti (ELT in Focus, 2020)
This research was conducted to investigate students’ reading interest on English reading materials through their reading habits during a Covid-19 pandemic. It also discovers contents of English reading materials that students most like to read. Survey research design was conducted by the researcher to investigate 98 students of 9 high schools in Subang. The data were collected using questionnaire that was distributed through social media in the form of Google Form link. It was found that 42.9% of the participants have the motivation as well as the willingness, and half (49%) of the total number of the participants get pleasure from reading English materials. Although 33.7% students do not accustom to read English materials outside English classes, it was embodying students’ reading habit which 60 students only read 2 – 3 days a week with the most answer of length less than an hour (41 Students). There are 38 students selected ‘articles on internet’ and 36 students selected ‘academic books’ as their favourite types of reading. Afterward, reading genres the students most selected are ‘education’ (44 students) and ‘entertainment’ (19 students), the rest of them selected poetry, horror, romance, humour, science fiction and other.